Evaluasi Kinerja Mesin Circular Loom Guna Mengurangi Defect Produk dengan Metode Six Sigma - Nafis, Randy Alwan; Purnama, Jaka (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. XYZ experienced a high level of defects in woven bag products, with a total of 846,929 defective units from 6,305,102 production units during January - May 2025. The dominant types of defects were keperet, loose knitting, perforated knitting, and insulation joints. This study aims to evaluate the performance of the Circular Loom machine to reduce defects using the Six Sigma method through the DMAIC approach. The analysis was carried out using Pareto diagrams, p control charts, DPMO calculations, and sigma levels. The calculation results showed that the Defect Per Million Opportunity (DPMO) value in the Wovenbag production process at PT.XYZ during the January - May 2025 period reached an average of (33,581), with the types of defects Keperet (38.515), Loose Knitting (32.987), Knitting Holes (30.711), and Insulation Joints (32.112), then the average Sigma Level (3.332) with the types of defects Keperet (3.268), Loose Knitting (3.339), Knitting Holes (3.370) and Insulation Joints (3.351). Average Process Capability (1.111) with the types of defects Keperet (1.089), Loose Knitting (1.113), Knitting Holes (1.123) and Insulation Joints (1.117).